DNA barcoding of rare and endangered plant species of the Republic of Kazakhstan - Sarsen, A.; Saginova, M.; Aktayeva, S.; Akishev, Zh.; Kiribayeva, A.; Manabayeva, Sh.; Mussakhmetov, A.; Kakimzhanova, A.; Khapilina, O.; Akhmetollayev, I.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2022)
The ability to identify vegetation types is very important for the study of flora biodiversity. DNA barcoding makes it possible to standardize the identification procedure by reference DNA regions. The most popular sequences for molecular identification and phylogenetic studies are Internal Transcribed Spacer (ITS) sequences. ITS are widely used as a phylogenetic marker to classify plants at various taxonomic levels, including genus, species, and subspecies. 29 samples of rare and endangered plant species were collected from Aksu-Zhabagly State Nature Reserve, Sayram-Ugam National Park and Berikkara Tract State Nature Reserve. DNA was isolated by the CTAB method, oligonucleotides flanking the ITS region of the nuclear DNA region were selected and synthesized. Sequencing was carried out and ITS sequences of the region were obtained for 29 species of rare and endangered plant species in Kazakhstan.